2012 IV International Conference "Problems of Cybernetics and Informatics" (PCI) 2012
DOI: 10.1109/icpci.2012.6486444
|View full text |Cite
|
Sign up to set email alerts
|

New heuristic algorithm for unweighted minimum vertex cover

Abstract: The minimum vertex cover (MVC) problem belongs to the class of NP-complete graph theoretical problems, which plays a central role in theoretical computer science and it has numerous real life applications. We are unlikely to find a polynomial-time algorithm for solving the vertex-cover problem exactly. In this paper, a fast heuristic algorithm, called Isolation Algorithm (IA), has been designed to find the minimum vertex cover of a graph. The IA has been tested on DIMACS benchmark graphs and BHOSLIB instances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…In this section, we investigate studies related to vertex cover and its varieties. In [26], isolation algorithm that is a heuristic method aiming to solve minimum VC problem has been proposed. Measurements taken on widely used datasets revealed that the proposed algorithm performs well when the graph size is small.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we investigate studies related to vertex cover and its varieties. In [26], isolation algorithm that is a heuristic method aiming to solve minimum VC problem has been proposed. Measurements taken on widely used datasets revealed that the proposed algorithm performs well when the graph size is small.…”
Section: Related Workmentioning
confidence: 99%
“…In spite of this growing attention, there does not currently exist a method for computing src(G) in general graphs G. Previous work on variants of the rainbow connection problem have proposed heuristic methods to produce rainbow colorings [5,10,36]. However, even in the event that these methods find an optimal solution, they are unable to provide certificates of optimality.…”
Section: Background and Motivationmentioning
confidence: 99%
“…To the best knowledge of the authors, no heuristic method has been proposed for strong rainbow connection in general graphs. Polynomial heuristic methods have been proposed for several related problems however, including the rainbow vertex connection problem [36] and the rainbow connection problem, both in general graphs [5] and in the special case of maximal outer planer graphs [10]. Since the upper bounds provided by heuristic methods can often be used to significantly assist with the computational methods, it is desirable to also have a heuristic method for strong rainbow connection.…”
Section: A Fast Random Heuristic For (Strong) Rainbow Connectionmentioning
confidence: 99%
“…As the size of the problem increases, these methods become futile. Meta-heuristics are powerful search methods which can be efficiently in providing satisfactory solutions to large and complex problems such as vertex cover [20], dominating set [14] and edge coloring [16] in a reasonable time. However, up to the authors' knowledge, there are no studies up to day used meta-heuristic techniques for solving the MWEDS problem.…”
Section: Introductionmentioning
confidence: 99%